IPv6+ based intelligent IP network solution - Chenxi WANG; Rui GU; Yaqun XIAO; Weibo WANG; Xiaofei WANG; Yue LIU (Dianxin kexue)
With the advent of the fourth industrial revolution,human society is gradually marching towards the fully connected,intelligent era.The intelligent era needs more automated and intelligent IP network,and the IPv6+ technology family represented by SRv6/BIERv6 is the key foundation for enabling a new generation of IP networks.The technical connotation of IPv6+ was comprehensively described,Huawei's innovation and thinking on IPv6+ solutions were relied on,key technologies and typical applications of IPv6+ in multiple solution scenarios such as simplified connection,SLA guarantee,private network experience,quality perception,and cloud-network integration,helping 5G and cloud business development were introduced.